Putra Specialist Hospital (M) Sdn Bhd / Siti Aminah Abd Kahar - Abd Kahar, Siti Aminah (Faculty of Business and Management, 2025)
As part of the requirements for all undergraduate programs in the Faculty of Business and Management, completing an internship is mandatory. This internship must be relevant to the student's academic major and area of concentration. The purpose of this course is to provide practical experience and develop workplace skills by engaging in company-assigned tasks, thus enhancing the student's practical abilities, knowledge, and professional attitude. I have completed my Industrial Training Report for my internship at Putra Specialist Hospital Melaka at Facility Engineering Department. I started my internship in September 2024, and through my experience, I have found this company to be an excellent environment for career and skill development. Putra Specialist Hospital Melaka is dedicated not only to producing high-quality products but also to fostering a supportive culture and environment. The various departments are well-coordinated, and the management is open to providing opportunities and sharing information, which has enabled me to perform effectively. In conclusion, the SWOT Analysis section evaluates both the positive and negative factors within and outside the organization, demonstrating the relevance of this analysis to understanding the overall situation.